Molecular detection of accessory gene regulator (AGR) staphylococcus in biofilm formation / Noramira Azmi - Azmi, Noramira (2017)
Staphylococcus epidermidis is gram positive bacteria and it is the most frequent cause of nosocomial infections due to indwelling medical devices and its dealings with human innate host. S.epidermidis is main virulence factor cause biofilm formation. Biofilm is a group of microorganism stick to each other and adhere to cell surface. Biofilm development process in three steps which is initial adhesion, intercellular aggregation and accumulation, and final detachment. S.epidermidis controls the expression of clusters of virulence genes using the accessory gene regulator (Agr) quorum-sensing in biofilm formation. A sample Staphylococcus epidermidis bacterial DNA was extracted using boiling method. Real-Time Polymerase Chain Reaction (qPCR) will be useful for the detection of agr in Staphylococcus epidermidis. The application of real-time PCR proved a rapid and specific method for the detection agr Staphylococcus epidermidis in biofilm formation